Management of continuous use medication by elderly users of a Basic Health (Research, Society and Development, 2023)
Introduction: The use of continuous medications in the daily lives of elderly individuals requires attention from healthcare professionals. This is primarily due to the effectiveness of treatment, which depends on the proper understanding and management of dosage, interactions, and other factors that can impact an individual's health. Objective: To understand the perception of elderly individuals using the local public healthcare system regarding the continuous medication management process. Methodology: A study with an observational descriptive design and qualitative analysis. Data were collected through semi-structured audio-recorded interviews, later transcribed. Analysis categories included understanding of health condition, medication management, and guidance received from healthcare professionals. Results: Twenty-one users of a public pharmacy in a health unit in a municipality in RS were interviewed, including 12 females and 9 males aged between 70 and 85, with 12 living with at least one family member and 9 living alone. The interviews revealed significant factors related to the recognition of the diagnosis and medication use, as well as aspects such as self-care and gender. The delivery of prescriptions was understood as the medical explanation of medication use. Conclusion: Managing continuous medications in older users highlights the need for attention and prompts the healthcare team to seek strategies for healthcare tailored to the specific needs of this group.